Mixed Methods Exploratory Study: Analisis Penerapan Budaya Keselamatan Pasien - I Made, Dwi Saputra; Hidayat, Dasrun; Santoso, Budi (STIKes Hamzar, 2025)
Patient safety is a fundamental principle in healthcare services and a global challenge. This study analyzes the implementation of a patient safety culture at BIMC HospitalKuta. Using a mixed-methods approach with a sequential exploratory design, qualitative data were collected through in-depth interviews and observations of the nursing director, safety officer, head nurse, and implementing nurses. Qualitative analysis was conducted using the Miles and Huberman model, followed by quantitative research using the HSOPSC questionnaire which was analyzed descriptively. Qualitative findings indicate that the patient safety culture in this hospital has been integrated into the staff's work habits, despite challenges such as fear of sanctions when reporting incidents and technical issues with the electronic reporting system. On the other hand, the quantitative results show a positive perception, with a Mean of 4.602 and a Median of 5.000 for positive statements, as well as a Mean of 1.347 with a Median of 1.000 for negative statements, indicating that respondents do not perceive any obstacles in the implementation of the patient safety culture. The difference in results between qualitative and quantitative research is caused by differing individual and public perceptions. The implementation of a safety culture in this hospital is influenced by nursing leadership and management support, with an effective incident reporting system through the MedBlaze platform that prioritizes the principles of just culture.